A COMPARATIVE STUDY OF THE FINANCIAL PERFORMANCE BANKS IN INDONESIA DURING COVID 19 PANDEMIC - Hartato Rianto; Hernawaty Hernawaty; Bagus Pangestu (Jurnal Scientia, 2023)
This study will examine the comparison of the financial performance of Islamic commercial banks (BUS) in Indonesia before and after the Covid 19 pandemic. The purpose of this study is to look at the resistance of Islamic commercial tires during the covid 19 pandemic. quantitative. Quantitative method is a research method using numerical data, namely the financial statements of commercial banks and Islamic commercial banks before and after the Covid-19 pandemic in the 2018-2020 financial reporting period, which added emphasis on objective measurement of results accompanied by statistical analysis. LDR is not significantly different between before and during the Covid-19 pandemic, there is an increase in LDR during the Covid-19 pandemic This can be interpreted that the pandemic has an effect on increasing LDR. ROA is not significantly different between before and during the Covid-19 pandemic. This means that the pandemic has no effect on increasing ROA, due to the level of turnover of assets used and operating profit expressed as a percentage and the amount of net sales. CAR is not significantly different between before and during the Covid-19 pandemic, there is an increase in CAR during the Covid-19 pandemic. This can be interpreted that the pandemic has no effect on increasing CAR. In other words, banks listed on the Indonesia Stock Exchange are still able to maintain CAR due to the Covid-19 pandemic.